Emergency care accessibility for road accidents victims: a review - Aisyah Putri Rahvy; Ascobat Gani (Emergency Care Journal, 2023)
Road traffic accident has become a public health concern. More than 80% injury-related deaths occurred in low-middle income countries (LMICs). Despite its importance, emergency care accessibility for road crash victims is still questionable. This study aims to review emergency care accessibility from approachability, acceptability, availability, affordability, and appropriateness dimensions for crash victims. This is a scoping review with literatures extracted from ScienceDirect, ProQuest, and Scopus. Articles analyzed using PCC (Problem/Population, Concept, Context) of scoping review. 1544 articles identified from databases of which 81 are relevant for full-text screening. The final 12 articles were eligible to be reviewed. Although emergency care is available in most areas, its existence was not well-known. Victims and helpers are treated unfairly in emergency care. Emergency care system also lacks clear coordination and it does not give appropriate treatment in timely manner. There was little evidence of how accessible emergency care to crash victims. Most studies only examined the availability of emergency care without comparing its actual utilization and other determinants impacting its accessibility. Future study should aim to assess approachability, acceptability, affordability, and appropriateness of emergency care. Strengthening emergency care from all dimensions is important to ensure its accessibility.